1996
DOI: 10.1056/nejm199612263352602
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in the Interferon-γ –Receptor Gene and Susceptibility to Mycobacterial Infection

Abstract: Four children with severe mycobacterial infections had a mutation in the gene for interferon-gamma receptor 1 that leads to the absence of receptors on cell surfaces and a functional defect in the up-regulation of tumor necrosis factor alpha by macrophages in response to interferon-gamma. The interferon-gamma pathway is important in the response to intracellular pathogens such as mycobacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
650
2
15

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,097 publications
(691 citation statements)
references
References 30 publications
17
650
2
15
Order By: Relevance
“…Studies in man have identified mutations in the gene IFNGR1 in Mendelian inheritance of susceptibility to disseminated atypical mycobacterial infection. 13 Results presented here suggest that polymorphism at IFNGR1 is associated with susceptibility to PKDL but not to underlying VL. Again, further work is required to verify this result and to identify the diseaseassociated mutation/polymorphism in this population.…”
Section: Discussionmentioning
confidence: 55%
“…Studies in man have identified mutations in the gene IFNGR1 in Mendelian inheritance of susceptibility to disseminated atypical mycobacterial infection. 13 Results presented here suggest that polymorphism at IFNGR1 is associated with susceptibility to PKDL but not to underlying VL. Again, further work is required to verify this result and to identify the diseaseassociated mutation/polymorphism in this population.…”
Section: Discussionmentioning
confidence: 55%
“…26,27 Individuals homozygous for the mutation have a greatly enhanced susceptibility to mycobacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several Salmonella serotypes have been identified and include Salmonella Paratyphi 139,140 or non-typhoid Salmonella serotypes such as Salmonella Typhimurium, 140 Salmonella Enteritidis, 139,[141][142][143] Salmonella group B 139,140 or untyped Salmonella. 139,144,145 Host resistance loci identified using QTL analysis…”
Section: Cytokines: Tnf Ifng and Il12mentioning
confidence: 99%